(untitled) (Eurasian Journal of Ecology, 2018)
In this article was investigated about plant morphological description, the soil mechanical structure, of nutrient elements and organically structure of soil cover the Kerbulak gorge. Also morphological description of the soil profile. The article was data general description of the direction of evolution of soil mechanical structure of nutrient elements and an organically things. Are presented the morphological characteristics of the soil profile. We was analyzed morphological structure of gray soils the foothill plains Malaysary ridge and floodplain soils of the Ili-River. The study area characterized a variety of desert vegetation. The part of the plant associations found Turan Artemisia, Burgun, boyalych, Kokpek, Shagir, prostrate summer cypress and other salsola plants. In the gorge Kerbulak common plants of 40 families, 130 genera and 163 species. With this is found the gorge endangered, relict and endemic species. In this study research object is located in the the northern part of the riverbed the sands of Sary-Esik Atyrau, south-eastern part of the mountain Tasmuryn, in the north-western and northern part bordering on the water area of Lake Balkhash, gorge Kerbulak with gray soils and takyr-like and sandy soils desert areas with characteristic vegetation. Key words: amorphous, hydromorphic, soil cover plants, floodplain soils, river or intra zonal ridges, endemic, relic, flora, fodder, medicines and other.